Verbatim Record of the First Part of the Thirteenth Meeting (Closed) - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Special Committee on the Problem of Hungary Witness A , a Social Democrat, made a statement about the events of the revolution in the Baranya region. The committee asked him questions about his participation in the national opposition movement during World War II which led to his arrest in 1944, about his arrest in 1951, and the aims and participants of the revolution in general. Witness B, a journalist, made a statement. He was asked about the role of the Petőfi circle and the writers' union at the beginning of the revolution, and the demonstrations on the first day of the revolution.